2016
DOI: 10.1098/rspb.2016.1676
|View full text |Cite
|
Sign up to set email alerts
|

Matrilineal inheritance of a key mediator of prenatal maternal effects

Abstract: Sex-linkage is predicted to evolve in response to sex-specific or sexually antagonistic selection. In line with this prediction, most sex-linked genes are associated with reproduction in the respective sex. In addition to traits directly involved in fertility and fecundity, mediators of maternal effects may be predisposed to evolve sex-linkage, because they indirectly affect female fitness through their effect on offspring phenotype. Here, we test for sex-linked inheritance of a key mediator of prenatal matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Several lines of evidence suggest heritability of and natural selection on yolk hormone concentrations. Field and laboratory studies with wild birds showed that yolk androgen concentrations are heritable and under natural selection (Ruuskanen et al, ; Tschirren, Sendecka, Groothuis, Gustafsson, & Doligez, ); directional selection for high or low yolk androgen concentrations in domesticated Japanese quail ( Coturnix japonica ) yielded rapid divergence of titers within a few generations (Okuliarova, Groothuis, Škrobánek, & Zeman, ) and indicates matrilineal inheritance (Tschirren et al, ) ; and artificial selection for behavioral traits such as bold and shy personalities in Great tits ( Parus major ) resulted in increasing, respectively, decreasing yolk androgen concentrations over the laying sequence (Groothuis, Carere, Lipar, Drent, & Schwabl, ). These results prompt us to propose that differential environments operating in urban versus rural populations lead to coupled changes in yolk androgen concentrations and behavior, the mechanistic link being the wide‐spread and well‐established organizational actions of steroid hormones on brain function during development of vertebrates (Adkins‐Regan, ; Fowden & Forhead, ; McCarthy, ; O'Connor & Barrett, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest heritability of and natural selection on yolk hormone concentrations. Field and laboratory studies with wild birds showed that yolk androgen concentrations are heritable and under natural selection (Ruuskanen et al, ; Tschirren, Sendecka, Groothuis, Gustafsson, & Doligez, ); directional selection for high or low yolk androgen concentrations in domesticated Japanese quail ( Coturnix japonica ) yielded rapid divergence of titers within a few generations (Okuliarova, Groothuis, Škrobánek, & Zeman, ) and indicates matrilineal inheritance (Tschirren et al, ) ; and artificial selection for behavioral traits such as bold and shy personalities in Great tits ( Parus major ) resulted in increasing, respectively, decreasing yolk androgen concentrations over the laying sequence (Groothuis, Carere, Lipar, Drent, & Schwabl, ). These results prompt us to propose that differential environments operating in urban versus rural populations lead to coupled changes in yolk androgen concentrations and behavior, the mechanistic link being the wide‐spread and well‐established organizational actions of steroid hormones on brain function during development of vertebrates (Adkins‐Regan, ; Fowden & Forhead, ; McCarthy, ; O'Connor & Barrett, ).…”
Section: Discussionmentioning
confidence: 99%
“…; Tschirren et al. ), then sex‐limited selection in one sex will have little impact on the fitness of the other sex. However, if sexually dimorphic reproductive function has a shared developmental (Gilbert ; Smith and Sinclair ) and/or genetic basis (Land ; Simmons ; Fischer et al.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating such intersexual effects on evolutionary trajectories, however, is crucial for our understanding of how male and female fitness evolves (Cox 2014). If strong sexual dimorphism reflects the independent genetic basis of male and female reproductive function Postma et al 2011;Moghadam et al 2012;Tschirren et al 2016), then sex-limited selection in one sex will have little impact on the fitness of the other sex. However, if sexually dimorphic reproductive function has a shared developmental (Gilbert 2000;Smith and Sinclair 2004) and/or genetic basis (Land 1973;Simmons 2003;Fischer et al 2009) then the intersexual consequences of sex-limited selection on the fitness of the other sex may be substantial.…”
Section: Introductionmentioning
confidence: 99%